Transatlantic diplomacy in securitisation of shale gaz's political risks - Dikarev, Oleksandr Ivanovych (My University, 2013)
Recent changes in energy markets are associated with new environmental regulations, raw material shortages, rising prices, and the exploitation of unconventional gas and oil. This has had a significant impact on the strategies of states and companies. It seems that new rules of the game have been established in global and regional energy markets since the global financial crisis of 2008. In 2013, we can see some illustrations of this process in the transatlantic negotiations between the United States and Canada with the EU. Останні зміни на ринках енергетичних ресурсів пов'язані з новими нормами захисту природи, дефіцитом сировини, зростанням цін, експлуатацією нетрадиційних газу та нафти. Це значно вплинуло на стратегії держав та фірм. Схоже на встановлення нових правил гри на світових та регіональних ринках енергетичних ресурсів після глобальної фінансової кризи 2008 року. У 2013 році деякі ілюстрації цього процесу ми можемо побачити в трансатлантичних переговорах між США та Канадою з ЄС.
Keywords: shale gas; сланцевий газ; geoeconomic strategy; геоекономічна стратегія